Using Game Engine for Online 3D Terrain Visualization with Oil Palm Tree Data - Che Mat, Ruzinoor; Mahayudin, Mohd Hafiz (Universiti Teknikal Malaysia Melaka, 2018)
Nowadays, cartography, otherwise known as mapping, are serving people in multiple aspects of livelihood and administration like planning, rescue, military, and tourism. The information is usually presented in the map by using legends, elevation, and contour.With the passage of time, many new methods of mapping are introduced which are divided into the non-digital and digital version.Another method used is the incorporation of 3D modelling in virtual aspect by simulating real-world data.In the recent years using the game engine is one of the important 3D modelling approaches obtained.The game engine has a lot more capabilities to simulate real-world terrains whereas using database support for terrain visualisation, new functionality can be used. This article discussed how to utilise game engine technology for developing 3D terrain visualisation with oil palm tree data.With the success of the system, it, therefore, gives benefits to potential visitors especially the manager of oil palm plantation, decision makers and planners to explore the online 3D terrain visualisation with oil palm tree data and manage it.